Muon neutrino disappearance at T2K. (March 2015) - Dealtry, T
Abstract: The T2K experiment has observed the disappearance of muon neutrinos from the J-PARC muon-neutrino beam. Using data corresponding to 3.01 × 10 20 protons on target, 58 muon neutrino event candidates were observed; 205 ± 17 (syst.) events are expected under the no-oscillation hypothesis. A fit to the observed rate and energy spectrum in a neutrino oscillation framework with three active neutrino flavours in constant density matter, assuming the normal mass hierarchy, yields a best fit mixing angle sin 2 θ 23 = 0.514 ± 0.082 and best fit mass squared splitting |Δ m 2 32 | = 2.44 +0.17 −0.15 × 10 -3 eV 2 /c 4, which corresponds to the maximal disappearance probability.